Paracoccidioidomicose em paciente com carcinoma do colo uterino - Marques, Silvio Alencar [UNESP]; Lastoria, Joel Carlos [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Sociedade Brasileira de Dermatologia, 2011)
Os autores relatam caso de paciente do sexo feminino com paracoccidioidomicose, associada a carcinoma do colo uterino estádio IIIB. Paracoccidioidomicose, associada à neoplasia, ocorre entre 0,16% a 14,1% segundo diferentes séries de casos. em casos com neoplasia disseminada a infecção fúngicas pode apresentar comportamento oportunístico

This report describes the case of a female patient with paracoccidioidomycosis associated with a stage IIIB cervical carcinoma. Paracoccidioidomycosis in association with a malignant tumor occurs in 0.16% to 14.1% of cases in accordance with different case series. In cases in which the cancer is disseminated, the fungal infection may behave opportunistically
Paracoccidioidomycosis in a patient with cervical cancer
Keywords: Carcinoma; Micoses; Neoplasias do colo do útero; Paracoccidioidomicose; Carcinoma; Mycosis; Paracoccidioidomycosis; Uterine cervical neoplasms